Role of Methylprednisolone for Covid-19 Patients Admitted to a Tertiary Care Hospital - Arshad, Komal; Humayun, Zill e; Kamran, Sultan Mehmood; Ifikhar, Raheel; Yousaf, Ali; Sajid, Muhammad Usman (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the role of Methylprednisolone in managing COVID-19 patients.Study Design: Cross-sectional study.Place and Duration of Study: Pakistan Emirates Military Hospital (PEMH), Rawalpindi Pakistan, from Jan to Feb 2021.Methodology: This study was carried out at the Department of Medicine. Medical records of all moderate, severe and critical COVID-19 patients admitted and receiving Methylprednisolone were reviewed. Methylprednisolone was used in all patients at doses 0.-2 mg per kg.Results: A total of 200 cases were included. The most common presenting symptoms were cough (77.5%), fever (67.5%) and shortness of breath (63.5%). Most patients (85%) presented within the first week of their illness. One or more comorbidities were present in 75% of patients. Most common being hypertension in 70(35%) and diabetes mellitus in 63(31.5%).Complications seen in the study were Cytokine release storm 92(46%) and acute respiratory distress syndrome 44(22%). The median time for initiation of corticosteroid therapy was 4 hours (range 1-96 hours). Overall survival (OS) in the study was 83.5%. OS for patients with moderate, severe and critical diseases was 97.8%, 86.2% and 62%, respectively (p